The association between physical exercise and health care seeking behavior in older adults: the mediating role of self-perceived health - Jian Li; Xing Zhao; Hongjuan Li (Frontiers in Public Health)
BackgroundAs global aging accelerates, the health of older adults has become a critical issue. Physical exercise has long been recognized for positive effects on health, particularly among the older adults. However, the specific impact of physical activity on health care seeking behavior, as well as the mechanisms underlying this relationship, remains insufficiently explored. This study investigates the effect of physical activity on health care seeking behavior in older adults and explores the mediating roles of physical and mental health.MethodsUsing data from the 2021 China General Social Survey (CGSS), this study employs regression analysis, and mediation analysis to examine how physical activity influences the health care seeking behavior of older adults. The analysis includes the evaluation of physical and mental health as mediators in this relationship. Additionally, heterogeneity analysis is conducted to explore differences across various age groups, and robustness tests are performed using lasso regression and ridge regression to ensure the stability of the results.ResultsThis study finds that physical activity negatively influences health care seeking behavior in older adults (β = −0.100, p < 0.001, 95%CI = [−0.154, −0.046]), with physical health (β = −0.026, 95%CI = [−0.087, −0.010]) and mental health (β = −0.008, 95%CI = [−0.074, −0.001]) acting as significant mediators. The effect of physical activity on health care seeking behavior is particularly pronounced in older adults aged 60–69 (β = −0.083, p = 0.027, 95%CI = [−0.158, −0.009]) and 70–79 (β = −0.154, p = 0.001, 95%CI = [−0.248, −0.060]). Robustness tests confirm the stability and reliability of the findings, with lasso regression and ridge regression further supporting the conclusions.ConclusionThe findings highlight the importance of physical activity in reducing health care seeking behavior and health management in older adults. By improving both physical and mental health, physical exercise can effectively reduce the medical seeking behavior of older adults. This study provides valuable insights for developing targeted health interventions and policies aimed at improving the health of older adults.